Dispersal of salmon lice (Lepeophtheirus salmonis Krøyer, 1837) egg strings from open‐cage salmon farming: A neglected source for infestation dynamics. (8th August 2020) - Eisenhauer, Lionel; Solvang, Torfinn; Alver, Morten; Franklin Krause, Daniel; Hagemann, Andreas
Abstract: The increasing number of Atlantic salmon farming locations in Norway has led to a complex dynamic network of sea lice infestation routes modulated by the local currents. Salmon lice ( Lepeophtheirus salmonis, Krøyer 1837) egg strings normally hatch from the distal end while still attached to the female louse; however, the female can release their egg strings if stressed during crowding and delousing events. Eggs continue developing normally after being detached. This paper presents empirical measurements of sinking velocities of L. salmonis egg strings of different lengths and maturities. Moreover, we evaluated the potential dispersal distance of detached egg strings from salmon net pens by numerical model simulations for different current flow rates to indicate how far released egg strings could disperse from salmon farms. Theoretical transport distance of egg strings varied between 250 m for the fastest sinking velocity of 11 mm/s and the lowest simulated horizontal current velocity of 0.05 m/s and 6.11 km for the lowest sinking velocity of 9 mm/s and the fastest horizontal velocity of 1 m/s. This study is the first to model egg string transport and to consider its role in larval sea lice dispersal and infestation dynamics.